The Effect of Income Shifting Incentives on Tax Avoidance - Febriyanti, Ria Syifa; Nurul Aisyah (ADPEBI, 2024)
This research aims to examine the effect of income-shifting incentives, which consist of multinationality, transfer pricing aggressiveness, thin capitalization, and intangible assets, on tax avoidance. This research uses the fixed effect model (FEM) method. The population in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019–2022 period, with a sample of 95 companies taken using the purposive sampling method. This research finds that the multinationality variable positively and significantly affects tax avoidance. Meanwhile, other variables do not have a significant effect on tax avoidance. This research was only conducted on manufacturing companies listed on the IDX in 2019–2022, so it cannot compare the conditions of all multinational manufacturing companies. This research can be a reference for future researchers on the same research topic. Apart from that, it is hoped that this research can be used in decision-making for companies that want to reduce the tax burden by practicing multinationality, transfer pricing aggressiveness, thin capitalization, or intangible assets.